A Secure Three-Factor User Authentication and Key Agreement Protocol for TMIS With User Anonymity. - Amin, Ruhul; Biswas, G. (Journal of Medical Systems, 2015)
Telecare medical information system (TMIS) makes an efficient and convenient connection between patient(s)/user(s) and doctor(s) over the insecure internet. Therefore, data security, privacy and user authentication are enormously important for accessing important medical data over insecure communication. Recently, many user authentication protocols for TMIS have been proposed in the literature and it has been observed that most of the protocols cannot achieve complete security requirements. In this paper, we have scrutinized two (Mishra et al., Xu et al.) remote user authentication protocols using smart card and explained that both the protocols are suffering against several security weaknesses. We have then presented three-factor user authentication and key agreement protocol usable for TMIS, which fix the security pitfalls of the above mentioned schemes. The informal cryptanalysis makes certain that the proposed protocol provides well security protection on the relevant security attacks. Furthermore, the simulator AVISPA tool confirms that the protocol is secure against active and passive attacks including replay and man-in-the-middle attacks. The security functionalities and performance comparison analysis confirm that our protocol not only provide strong protection on security attacks, but it also achieves better complexities along with efficient login and password change phase as well as session key verification property.